Pemaknaan Nelayan Atas Kemiskinan Kultural - Syawal Gani Yusuf; Lesti Heriyanti; Linda Safitra (Yayasan Literasi Sains Indonesia, 2025)
This study aims to examine the social construction of traditional fishermen related to poverty in the Teluk Segara area. Poverty is often understood as an objective condition and can be measured through economic indicators. However, in the context of traditional fishing communities, poverty is also influenced by social construction involving cultural values, social structures, and human relationships and their natural environment. By using a qualitative approach and case study method, this study explores how traditional fishermen in Teluk Segara interpret and deal with their daily poverty. This study aims to examine the social construction of poverty from the perspective of traditional fishermen, with an emphasis on case studies in coastal communities However, in the context of fishing communities, poverty is also a result of social construction influenced by cultural values, social structures, and human relationships with the surrounding natural environment. These findings provide valuable insights into the importance of understanding poverty in a more specific context, especially in communities with strong ties to nature and tradition. This study also emphasizes the need for more inclusive and community-based development policies, as well as empowerment efforts that respect local values. All of this aims to improve the welfare of traditional fishermen in Teluk Segara